LEGAL STUDY OF THE CRIMINAL ACT OF ADULTERY - Johan Alfred Sarades Silalahi; Novelina Mutiara Sariati Hutapea; Desy Kartika Caronina Sitepu (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This journal is entitled Legal Review of the Criminal Act of Adultery (Cohabitation) in the Perspective of Law Number 1 of 2023. The focus of the study in this journal is how the concept of Law Number 1 of 2023 as an effort to overcome the criminal act of adultery (cohabitation). This type of research is library research. The data sources in this study are primary data sources, namely from Article 412 of the New Criminal Code concerning cohabitation and secondary data sources from books, journals, books, and other sources that have relevance to the study in this research. The data collection technique in this study is a library technique. The results of this study indicate that the Criminal Sanctions are heavier, the criminal sanctions in Article 412 of the New Criminal Code should be heavier than Article 411 of the New Criminal Code. At least 2 times heavier than the maximum penalty in Article 411 of the New Criminal Code, the reason is that if you have lived together, it is certain that you will commit adultery repeatedly. If the criminal sanctions in Article 412 of the New Criminal Code are lighter than those in Article 411 of the New Criminal Code, couples who intend to commit adultery may prefer to cohabit because if caught, the maximum penalty is much lighter.